Tourism Industry: An Instrument of Indian Economic Growth through FDI - Deshwal, Dr. Parul (International Journal of Scientific Research and Management (IJSRM), 2015)
Tourism industry is the fastest growing industry of the world which brings the various growth prospects to the economy. After Globalization this industry grows tremendously as it opens many opportunities by connecting with various countries. While talking about Indian scenario, the hotel and tourism industries have been growing rapidly in recent years, bringing in huge revenues through overseas as well as domestic tourists in many parts of India. Tourism is one of the third largest revenue generators of foreign exchange for India and also employs one of the highest numbers of manpower while talking about Indian scenario; the hotel and tourism industries have been growing rapidly in recent years, bringing in huge revenues through overseas as well as domestic tourists in many parts of India. Tourism is one of the third largest revenue generators of foreign exchange for India and also employs one of the highest numbers of manpower. Conde Nast Traveler, one of the most decorated travel magazines, rated India as one of the hottest destination in the world. According to the World Tourism Organization, India will be the leader in the tourism industry in South Asia with 8.9 million arrivals by 2020. India is gradually emerging as the second most rapidly increasing (8.8 percent) tourism economy in the world over 2005-14 according to the World Travel & Tourism. This paper includes the study about the major contribution of tourism industry in the economic growth in the form of increased revenues, employment generation, poverty alleviation and women empowerment in environment sustainable manner which has multiplier effect in the economy.